(untitled) (International Journal of Engineering and Computer Science, 2015)
IPTV was convergence product between broadcasting, telecommunication and information technology because it gave multimedia service such as TV broadcasting, video, audio, text, and data transmitted by using IP protocol. IPTV service had a better quality than conventional TV, such as voice over internet protocol (VoIP), data (internet), and video on demand (VoD). IPTV is distinctly different from “Internet Video” that simply allows users to watch videos like movie previews and webcams, over the Internet in a “best effort” fashion with no into- end service management an quality of service considerations. This paper is an overview of the new emerging IPTV technology. Our future work will be focusing on IPTV Quality of Experience, its architecture security threats and its possible solutions and so on.